TRAJECTORY OF AGING COMMUNITIES: THE PATTERNS AND CHARACTERISTICS - Lee, Y (Innov Aging, 2018)
Objectives: While much research has been done on community-dwelling older adults, relatively less attention has been paid to the communities where older adults live. Of all the major cities in Canada, Calgary has the youngest population but the senior population is growing at a pace never seen before. This study examines the trajectory of growth in older adult population at the community level and investigates the characteristics of communities with high density of older adults. Methods: Using the census data from the 1991 to 2016 from Statistics Canada and spatial data from The City of Calgary, all analyses in this study was performed at the census tract level. Using a geographic information system (GIS), we map out how the communities have been changed over the last 25 years and identify the communities where older adults are likely to live. Results: Among the communities in Calgary, there are about 75% of communities with more than 7% of aged 65+ population. The growth in communities with older adults has spread out in the entire city and those communities are characterized as smaller household size, lower levels of incomes, fewer immigration population, lower levels of education, and fewer in the labor force. Discussions: The pattern of growth in communities with older adults and its characteristics have implications that older adults living in these communities might be more vulnerable. More emphasis should be put on community level to provide the purposes of longer lives for older adults.